Interaction in an Asynchronous Online Course: a Synthesis of Quantitative Predictors - Zingaro, Daniel; Oztok, Murat (Online Learning, 2012)
The effectiveness and potential of asynchronous online courses hinge on sustained, purposeful collaboration. And while many factors affecting interaction have been uncovered by prior literature, there are few accounts of the relative importance of these factors when studied in the same online course. In this paper, we develop a literature-informed model of six predictors on the likelihood that a note receives a reply. We corroborate earlier findings (such as the impact of the date that the note was posted) but also obtain one contradictory result (that reading ease does not appear to be a significant predictor). We offer hypotheses for our findings, suggest future directions for this type of research, and offer educational implications.